2005
DOI: 10.1007/s00125-005-1692-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pdx-1 perturbs proinsulin processing, insulin secretion and GLP-1 signalling in INS-1 cells

Abstract: Aims/hypothesis: Mutations in genes encoding HNF-4α, HNF-1α and IPF-1/Pdx-1 are associated with, respectively, MODY subtypes-1, -3 and -4. Impaired glucosestimulated insulin secretion is the common primary defect of these monogenic forms of diabetes. A regulatory circuit between these three transcription factors has also been suggested. We aimed to explore how Pdx-1 regulates beta cell function and gene expression patterns. Methods: We studied two previously established INS-1 stable cell lines permitting induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 79 publications
(114 reference statements)
11
46
0
Order By: Relevance
“…Since PDX-1 is essential for the regulation of a wide variety of important genes in b-cells (Waeber et al 1996, Watada et al 1996, Macfarlane et al 2000, a reduction in expression would be expected to exert deleterious effects on insulin secretory responses. Expression of dominant-negative PDX-1 in INS-1 cells has been shown to inhibit nutrient-and KCl-induced insulin secretion (Wang et al 2005). Monitoring of PDX-1 expression at the protein level in response to HNF1b confirmed that it declined markedly within 24 h, suggesting that turnover of PDX-1 protein occurs rapidly in cells overexpressing WT HNF1b.…”
Section: Discussionmentioning
confidence: 94%
“…Since PDX-1 is essential for the regulation of a wide variety of important genes in b-cells (Waeber et al 1996, Watada et al 1996, Macfarlane et al 2000, a reduction in expression would be expected to exert deleterious effects on insulin secretory responses. Expression of dominant-negative PDX-1 in INS-1 cells has been shown to inhibit nutrient-and KCl-induced insulin secretion (Wang et al 2005). Monitoring of PDX-1 expression at the protein level in response to HNF1b confirmed that it declined markedly within 24 h, suggesting that turnover of PDX-1 protein occurs rapidly in cells overexpressing WT HNF1b.…”
Section: Discussionmentioning
confidence: 94%
“…Homeodomain transcription factor PDX-1 is required for cAMP generation and exendin-4 stimulation of cyclin A2. PDX-1 is required for exendin-4 effects on ␤-cell proliferation and function (6,8,21). Therefore, we examined the role of PDX-1 in exendin-4 -stimulated cyclin A2 expression.…”
Section: Exendin-4 Stimulation Of Cyclin A2mentioning
confidence: 99%
“…␤-Cell-specific ablation of PDX-1 markedly reduces GLP-1-induced ␤-cell proliferation (8), whereas other salient ␤-cell properties, such as glucokinase activity, mitochondrial metabolism, ATP generation (21), and levels of mRNA transcripts of important proteins such as IRS2, CREB, and transcription factors Nkx2.2 and Isl1, remain intact at normal levels (8,21). Consistent with these observations (5,21), the present findings confirm that PDX-1 expression is required for cAMP generation in pancreatic ␤-cells.…”
Section: Exendin-4 Stimulation Of Cyclin A2mentioning
confidence: 99%
“…Based upon these studies, several mechanisms have been postulated: (a) increased β cell apoptosis via and Bcl-2), with resulting loss of downregulation of anti-apoptotic genes (Bcl XL functional cell mass [56,67], (b) loss of activity of key Pdx1 target genes whose products are involved in glucose-stimulated insulin transcription and secretion (including Glut2, glucokinase, MafA, Nkx6.1, insulin) [57,63,[68][69][70][71][72][73][74][75][76], and (d) loss of new β cell formation/regeneration [64,77]; in this regard, studies suggest that the action of glucagon-like peptide 1 (GLP1) in enhancing β cell growth and formation in the adult may rely upon activation of Pdx1 in β cells and potential precursor cell types, such as those residing within ducts [74,[78][79][80][81][82].…”
Section: Role Of Pdx1 In the Adult Pancreasmentioning
confidence: 99%